An investigation on the Impact of the Western Teachers’ Values and Cultures on Emirati Students’ Moral and Character Development - Ali, Salam Omar (2016)
The purpose of the study was to investigate the influence of the Western teachers’ values and cultures on the Emirati students’ character and moral development in the international schools that follow the British curriculum. Moreover, the study explored the UAE national students’ perceptions of character development in the international schools as well as investigated the Emirati parents’ perceptions of the influence of the Western teachers’ values on their children’s character and moral development. A total of forty- nine Western teachers, forty- nine UAE national students from different grades and forty nine parents participated in the quantitative part of the study. While in the qualitative part of the study, fifteen Western teachers, ten UAE national students and ten parents were interviewed in semi structured interviews to get deeper insights on the effect of the Western teachers on the students’ character and moral development. Statistical Package for Social Sciences (SPSS) programme was used to analyse the quantitative data, while the thematic interpretive approach was used to analyse the responses of the interviewees. Available documents related to character education, including ten lesson plans and behaviour polices of the three sample schools were analysed. Quantitative data suggested that the majority of parents believe that parents are the best teachers of character (mean of 1.55) and social skills are more important for their children than academic skills (mean of 1.73). Moreover, the quantitative data revealed that the majority of students do not treat each other with respect (mean of 2.32) and the majority of teachers do not treat students with respect (mean of 2.90). Students felt that their voice and thoughts are not heard and valued in their schools (mean of 2.65). While most of the teachers believe that character education enhances academic achievement (with a mean of 1.37) and develops good character (with a mean of 1.48). They also agreed (with a mean of 1.69) that teachers participate in providing character education to their students. iii The qualitative data revealed that the UAE national students are influenced by the values and the cultures of their Western teachers in various ways, including their personalities and their perspectives in life. According to the parents of the UAE national students, the Western teachers who act as role models for their children have impacted their children positively as well as negatively. The results also demonstrated that there is a big gap in the Western teachers’ knowledge about the UAE culture as their Western values and cultures are completely different from those in the UAE; therefore, this situation needs to be highlighted to make sure that the Western teachers’ teaching and practices do not contradict with what the Emirati students are expected to learn.